Síndrome de Burnout : um estudo com guias de turismo regional em Natal-RN - Souza, Rayssa Soares de (2011)
Burnout is a psychological syndrome triggered in response to continuous exposure to interpersonal stressors. It is considered a multifactorial construct, which is commonly characterized by three dimensions: emotional exhaustion, dehumanization, and lack of personal accomplishment.This study aimed to verify if the three characteristics of burnout (exhaustion, lack of dehumanization and personal accomplishment) are present in people working as guides Tourism in Natal - RN. It is a descriptive and quantitative study. 109 subjects were surveyed. Data collection was done through the use of questionnaires, the instrument used was the characterization of the Burnout Scale (ECB) created and validated in Brazil by Trocoli and Tamayo (2000). In order to analyze data we used descriptive statistics, analysis of core measures, exploratory and confirmatory factor analysis, reliability analysis, cluster analysis, multiple discriminant and Spearman correlation. Factor analysis identified four factors that explain 58.3% of the total variance. Those factors were named exhaustion, deception, avoidance, and dehumanization. The reliability of the instrument, as measured by Cronbach's Alpha was 0.918, which is considered excellent reliability. The 109 subjects were grouped into three cluster, which had the deception, avoidance, and dehumanization as discriminant. It is possible to conclude that the characteristics of burnout syndrome are present in the studied population where 19 people are on the high level of burnout, moderate in 32 and 56 in the light. The correlations between socio-demographic variables studied and the dimensions of burnout, were few and weak. The variable leave for health reasons in the study appeared to be related to feelings of exhaustion and avoidance behavior appeared related to younger individuals and who work only in the activity of Receptive Tourism Guide. Verification of the incidence of burnout in individuals surveyed suggest the need to adopt intervention strategies are individual, organizational and / or combined